Evaluation of physicochemical parameters of surface water quality in Gebeng Industrial Area, Pahang, Malaysia - Islam, Mir Sujaul; Salah, Masoud Gabar; Karim, Md Abdul; Mohamad Idris, Ali; Noram Irwan, Ramli (Bangladesh Botanical Society, 2018)
The contamination level in Gebeng watershed has increased due to industrialization and release of most of the wastewater from the industries, which are pollutants and dumped into the surface water. The present study was carried to evaluate the surface water quality of Gebeng industrial estate, Pahang, Malaysia. Principal component analysis classified the analysed parameters to 5 components according to the sources of pollutants and the correlation demonstrated on the relation between all these groups. Cluster analysis was grouped 10 monitoring sites into two groups (high and moderate pollution). Water quality of Gebeng was classified based on Water quality index (WQI), Malaysia as class III and IV, which are slightly polluted due to lower dissolved oxygen (DO) concentration, low pH value, and higher levels of Ammoniacal nitrogen (AN), Biochemical oxygen demand (BOD), Chemical oxygen demand (COD) and Total suspended solids (TSS). It is evident that sites IZ2, IZ3, HA1, HA2 and DS received the highest pollutants discharge from the industrial sectors.